Evaluation of non-cross linked xeno-free hyaluronic acid solutions as visco elastic biomaterials - Sunil Paramel Mohan; Arunkumar Palaniappan (Wolters Kluwer Medknow Publications, 2023)
Background: Hyaluronic acid (HA) is a naturally occurring biodegradable, high molecular weight, non-sulfated glycosaminoglycan (GAG) polymer known for its excellent biocompatibility. HA-based products are widely used as viscosupplements, dermal fillers, and ophthalmic lubricants in clinical settings. Although animal and bacterial-derived HA are commonly reported, plant-sourced HA is not frequently reported. In this study, we have evaluated various viscoelastic properties of one such plant-based HA solution and propose them as an alternative to existing animal/bacteria-sourced HA. Materials and Methods: The viscoelastic properties of plant-sourced HA solution of various concentrations (0.1%, 0.5%, 1%, and 2% in PBS) were studied using a rheometer at 37°C. Flow curves, amplitude sweep studies, and frequency sweep studies were performed and compared for all HA solutions. Results: The HA solutions displayed shear-thinning behavior, which is an important characteristic of an injectable biomaterial. The 0.1 and 0.5% HA were found to have viscoelastic properties appropriate for eye lubricants, while 1 and 2% HA solutions showed properties suitable for soft tissue fillers. Frequency sweep studies indicated that all the samples are typically viscoelastic liquids with a loss modulus (G") higher than the storage modulus (G'). This indicated that the samples needed further processing like crosslinking of HA or using higher molecular weight HA to be suitable as viscosupplements. However, the frequency sweep studies also indicated that these solutions can be used as soft tissue fillers of any type based on the G' and tan δ values. Conclusion: The plant-sourced HA solutions are found to exhibit good shear-thinning properties with viscoelastic properties suitable for eye lubricants and soft tissue fillers. However, to be used as viscosupplements, the viscoelastic properties of HA solutions have to be further modified through non-toxic crosslinking strategies, and hydrophobic derivatives as well as by using high molecular weight HAs.